Penile Necrosis, Military Medicine, and South Korean Participation in the Vietnam War, 1964–1973. Issue 4 (1st December 2017) - Kim, Jane S. H.
Abstract : This article examines the Korean medical history of the Vietnam War, particularly, the sexual activities and venereal disease control of the Republic of Korea Forces in Vietnam (ROKFV). For Ch'ae Myŏngsin, the commander of the ROKFV, the largest overseas military dispatch in the history of the South Korean military was an occasion to raise the profile of the infant Republic of Korea in the eyes of the world. However, the occasion also warranted possible sexual contact between South Korean soldiers and Vietnamese civilians and created potential complications. To caution the South Korean men away from Vietnamese women, Ch'ae circulated a mythical story about a fatal venereal disease endemic to Southeast Asia that specifically targets male genitalia. Using the theory of subimperialism and postcolonial readings of gender and colonialism, this article reads Ch'ae's story of penile necrosis against ROKFV records on sexual activities and venereal disease control to show how, in regulating sexual desires and bodily activities, the South Korean state came to replicate the colonizing practices of colonizers and reproduce imperialism as subimperialism in Cold War Asia.